Self-assembled modified polyolefin diaphragm as well as preparation method and application thereof

Through the preparation method of self-assembled modified polyolefin separators, the problems of insufficient thermal stability and mechanical properties of existing lithium-ion battery separators are solved, and higher battery cycle life and safety are achieved.

CN119581786AActive Publication Date: 2025-03-07JILIN NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411671109.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The polyolefin separators used in existing lithium-ion batteries have poor thermal stability and insufficient mechanical properties under high temperature conditions, resulting in battery safety problems and short cycle life.

Method used

The self-assembled modified polyolefin separator is used to prepare a self-assembled modified polyolefin separator, and the layered modified layer is formed by electrochemical methods, and the in-situ phase interface is transformed to form a stable interface layer.

Benefits of technology

It improves the chemical stability, mechanical strength and wettability of the diaphragm, inhibits the generation of metal lithium dendrites, extends the cycle life of the battery and improves the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581786A_ABST
    Figure CN119581786A_ABST
Patent Text Reader

Abstract

The invention relates to a self-assembled modified polyolefin diaphragm as well as a preparation method and application thereof, and belongs to the technical field of electrochemistry. The technical problems that in the prior art, a polyolefin diaphragm is poor in thermal stability, mechanical performance and wettability, the side reaction of an electrode-diaphragm interface is serious, and dendritic lithium dendrites easily cause internal short circuit of a battery are solved. The preparation method of the self-assembled modified polyolefin diaphragm comprises the following steps: performing deposition modification of layered hydroxide on the surface of the polyolefin diaphragm through vacuum filtration to obtain a modified layer, and performing phase interface conversion on the modified layer through an electrochemical in-situ method to form a stable transition interface layer. The preparation method has the advantages of low production cost, simple operation process and the like, and the diaphragm prepared by the method has good thermal stability, mechanical property and chemical activity, can inhibit dendritic crystal growth to realize long-life cycle of the battery, and is suitable for large-scale production and industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of electrochemical technology, and specifically relates to a self-assembled modified polyolefin diaphragm and a preparation method and application thereof, and in particular relates to the application of the self-assembled modified polyolefin diaphragm in a metal lithium battery. Background Art

[0002] In metal lithium batteries, the basic function of the separator is to prevent physical contact between the positive and negative electrodes, and to act as a carrier of the electrolyte to achieve ion transport. The separator does not directly participate in the electrochemical reaction inside the battery, but its structure and performance greatly affect the performance and life of the battery.

[0003] Among the existing lithium-ion batteries, the most widely used diaphragms are made of polyolefins, mainly microporous polyethylene (PE) and polypropylene (PP) diaphragms. Although polyolefin diaphragms have good porosity, which allows the electrolyte to infiltrate and pass through the micropores, the thermal stability of polyolefin diaphragms is relatively low, and they are prone to deformation under high temperature conditions, which can cause short circuits in the battery. Secondly, the mechanical properties of polyolefin membranes are poor and cannot prevent the formation of metal lithium dendrites. Under high current density, they are also easily pierced by metal lithium dendrites, causing battery safety issues. In addition, since polyolefin diaphragms have non-polar surfaces and low surface energy, the wettability and electrolyte retention rate of polyolefin diaphragms are also limited. The electrolyte cannot fully fill the microporous structure of the diaphragm, which increases the ion transfer resistance, thereby affecting the lithium ion transfer efficiency, resulting in a short battery cycle life and serious electrode-diaphragm interface side reactions. Summary of the invention

[0004] In view of this, the present invention aims to solve the technical problems in the prior art such as poor thermal stability, poor mechanical properties, poor wettability, serious side reactions at the electrode-membrane interface, and dendritic lithium dendrites that easily lead to internal short circuits of batteries of polyolefin diaphragms. The present invention proposes a self-assembled modified polyolefin diaphragm and a preparation method and application thereof. The self-assembled modified polyolefin diaphragm has good chemical stability, good mechanical strength, high specific capacity, and excellent cycle performance. The preparation method has the advantages of low production cost and simple operation process, and is suitable for large-scale production and industrial application.

[0005] The present invention solves the above technical problems, and the technical solutions adopted are as follows.

[0006] The present invention provides a method for preparing a self-assembled modified polyolefin diaphragm, comprising the following steps:

[0007] Step 1: Preparation of modified precursor sol

[0008] Firstly, a transition metal acetate hydrate and an alkali metal acetate are dissolved in anhydrous ethanol and mixed evenly to obtain a reaction mixture; then the reaction mixture is reacted at 40-80° C. under normal pressure, filtered after the reaction is complete, dried, and crushed to obtain a solid powder; finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonication is performed until the solid powder is completely dissolved to obtain a modified precursor sol;

[0009] In the reaction mixture, the concentration of transition metal ions is 10-40 mmol / L, and the concentration of acetate (Ac - ) concentration is 2 to 2.4 times the concentration of transition metal ions;

[0010] Step 2: Self-assembly modification of the diaphragm

[0011] The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol to obtain a modified liquid, a polyolefin microporous filter membrane is used as a suction filtration membrane, and the modified liquid is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled diaphragm, and vacuum drying is performed at 40 to 60° C.;

[0012] Step 3: Electrochemical phase transition of the membrane modification layer

[0013] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, and a lithium insertion reaction is performed for 2-5 cycles at a scan rate of 0.5-3 mV / s and a voltage range of 3.0 V to -0.2 V to obtain a self-assembled modified polyolefin membrane;

[0014] In the lithium-lithium symmetrical battery, the lithium salt concentration of the electrolyte is controlled to be 0.5-1.5 mol / L.

[0015] Preferably, in step 1, the transition metal acetate hydrate includes one or more of cobalt acetate tetrahydrate (CoAc2·4H2O), nickel acetate tetrahydrate (NiAc2·4H2O), and ferrous acetate tetrahydrate (FeAc2·4H2O).

[0016] Preferably, in step 1, the alkali metal acetate includes one or more of potassium acetate, sodium acetate and lithium acetate.

[0017] Preferably, in step 1, the mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:80 to 1:130.

[0018] Preferably, in step 2, the volume ratio of the modified precursor sol to anhydrous ethanol is 1:0.6 to 1:1.5.

[0019] Preferably, in step 2, the polyolefin microporous filter membrane includes one or more of a polyethylene membrane, a polypropylene membrane, a mixed polyolefin membrane, a cellulose membrane, a polyethersulfone membrane, and a polytetrafluoroethylene membrane.

[0020] Preferably, in step 2, the pore size of the polyolefin microporous filter membrane is 10 to 80 nm.

[0021] Preferably, in step 2, the vacuum drying is carried out at 40-60° C. for 12-24 hours.

[0022] Preferably, in step three, in the electrolyte of the Li-Li symmetric battery, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(trifluoromethylsulfonyl imide) (LiTFSI), and lithium trifluoromethanesulfonate (LiSFI); the solvent includes one or more of dimethyl carbonate (DMC), ethylene carbonate (EC), propylene carbonate (PC), 1,4-dioxolane (DOL), diethyl carbonate (DEC), dimethyl ether (DME), ethylene glycol dimethyl ether (EGDME), and tetraethylene glycol dimethyl ether (TEGDME).

[0023] The present invention also provides a self-assembled modified polyolefin membrane prepared by the method for preparing the self-assembled modified polyolefin membrane.

[0024] The present invention also provides application of the self-assembled modified polyolefin separator in metal lithium batteries.

[0025] The principle of the present invention is: firstly, the surface of the polyolefin diaphragm is modified by layer-by-layer self-assembly to form a layered modified layer, and then an in-situ phase interface transformation is performed by an electrochemical method to transform the layered modified layer into an electrochemically active modified layer, thereby forming a stable interface layer on the surface of the polyolefin diaphragm, thereby improving the stability between the diaphragm and the metal negative electrode, and at the same time inhibiting the growth of dendrites to achieve a long life cycle of the battery.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The preparation method of the self-assembled modified polyolefin diaphragm of the present invention includes self-assembly modification and electrochemical phase transition of the diaphragm, deposition modification of layered hydroxide on the surface of the polyolefin diaphragm is performed by a vacuum filtration device, and phase interface transformation is performed by an electrochemical in-situ method, so as to form a stable transition interface layer on the surface of the polyolefin diaphragm, thereby achieving the purpose of inhibiting the growth of metal lithium dendrites. The preparation method has simple process, simple equipment, short preparation cycle, environmental protection, low cost, high repeatability, is conducive to large-scale preparation, and has a very broad application prospect.

[0028] The self-assembled modified polyolefin membrane of the present invention is uniform and has good density; the surface modification of the polyolefin membrane can effectively improve the wettability of the electrolyte on the surface of the polyolefin membrane, and improve the mechanical strength, thermal stability and chemical activity of the polyolefin membrane; the surface modification layer of the polyolefin membrane can also be strengthened to inhibit the generation of metallic lithium dendrites, thereby greatly improving the stability of the negative electrode, extending the battery life and rate performance.

[0029] The results of lithium symmetry experiments and lithium iron phosphate experiments show that the self-assembled modified polyolefin separator of the present invention is used in metal lithium batteries and exhibits excellent performances such as lower polarization, longer cycle time, and higher capacity. It can significantly improve the battery's capacity, cycle performance and other characteristics, and plays an important role in improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some specific implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a SEM cross-sectional image of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention;

[0032] Figure 2 The AFM surface images of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention, the left image is a surface roughness analysis image, and the right image is a surface morphology image;

[0033] Figure 3 This is a BET image of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention;

[0034] Figure 4 The electrochemical performance of a symmetrical battery with a self-assembled modified polyolefin separator prepared in Example 1 of the present invention is compared with that of a symmetrical battery with a commercial unmodified separator. DETAILED DESCRIPTION

[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings.

[0036] In the following examples, various processes and methods not described in detail are conventional methods known in the art. Unless otherwise specified, the materials, reagents, devices, instruments, equipment, etc. used in the following examples can be obtained from commercial sources.

[0037] Example 1

[0038] Step 1: Preparation of modified precursor sol

[0039] First, cobalt acetate tetrahydrate, sodium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 1:0.2:80, and then reacted at 52° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:95.

[0040] Step 2: Self-assembly modification of the diaphragm

[0041] The modified precursor sol prepared in step 1 was mixed evenly with anhydrous ethanol in a volume ratio of 1:1.2 to obtain a modified solution, and a commercial Celgard-2500 microporous membrane was used as a suction filtration membrane, and the modified solution was used as a filtrate, and vacuum-filtered to obtain a self-assembled membrane, and vacuum-dried at 40-60° C. for 20 h;

[0042] Step 3: Electrochemical phase transition of the membrane modification layer

[0043] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, metallic lithium is used as the electrode, and an electrolyte prepared by dissolving 1M LiTFSI in DOL / DME (volume ratio 1:1) is used as the working electrolyte. Two cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation is obtained.

[0044] Figure 1 This is a SEM cross-sectional image of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention; Figure 2 The AFM surface images of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention, the left image is a surface roughness analysis image, and the right image is a surface morphology image; Figure 3 This is the BET image of the self-assembled modified polyolefin membrane prepared in Example 1 of the present invention.

[0045] Example 2

[0046] Step 1: Preparation of modified precursor sol

[0047] First, nickel acetate tetrahydrate, lithium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 0.3:0.2:80, and then reacted at 70° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen is removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen is removed is 1:100.

[0048] Step 2: Self-assembly modification of the diaphragm

[0049] The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol in a volume ratio of 1:1 to obtain a modified solution, and a commercial Celgard-2500 microporous membrane is used as a suction filtration membrane, and the modified solution is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled membrane, and vacuum drying is performed at 40-60° C. for 20 h;

[0050] Step 3: Electrochemical phase transition of the membrane modification layer

[0051] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, metallic lithium is used as the electrode, and an electrolyte prepared by dissolving 1M LiTFSI in DOL / DME (volume ratio 1:1) is used as the working electrolyte. Two cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation is obtained.

[0052] Example 3

[0053] Step 1: Preparation of modified precursor sol

[0054] First, nickel acetate tetrahydrate, sodium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 1:0.2:90, and then reacted at 70° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen is removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen is removed is 1:100.

[0055] Step 2: Self-assembly modification of the diaphragm

[0056] The modified precursor sol prepared in step 1 was mixed evenly with anhydrous ethanol in a volume ratio of 1:0.5 to obtain a modified solution, and a commercial Celgard-2325 microporous membrane was used as a suction filtration membrane, and the modified solution was used as a filtrate, and vacuum-filtered to obtain a self-assembled membrane, and vacuum-dried at 40° C. for 16 to 18 hours;

[0057] Step 3: Electrochemical phase transition of the membrane modification layer

[0058] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, using metallic lithium as the electrode, and using 1M LiClO4 dissolved in EC / DEC / PC (volume ratio 1:1:1) electrolyte as the working electrolyte. Four cycles of lithium insertion reaction are carried out at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally obtain a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation.

[0059] Example 4

[0060] Step 1: Preparation of modified precursor sol

[0061] First, ferrous acetate tetrahydrate, lithium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 0.8:0.1:80, and reacted at 40° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:89.

[0062] Step 2: Self-assembly modification of the diaphragm

[0063] The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol in a volume ratio of 1:1 to obtain a modified solution, and a commercial Celgard-2325 microporous membrane is used as a suction filtration membrane, and the modified solution is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled membrane, and vacuum drying is performed at 40-60° C. for 20 h;

[0064] Step 3: Electrochemical phase transition of the membrane modification layer

[0065] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, metallic lithium is used as the electrode, and an electrolyte prepared by dissolving 1M LiTFSI in DOL / DME (volume ratio 1:1) is used as the working electrolyte. Three cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation is obtained.

[0066] Example 5

[0067] Step 1: Preparation of modified precursor sol

[0068] First, nickel acetate tetrahydrate, potassium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 1:0.1:90, and reacted at 70°C under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen is removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen is removed is 1:108.

[0069] Step 2: Self-assembly modification of the diaphragm

[0070] The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol in a volume ratio of 1:1.3 to obtain a modified solution, and a commercial cellulose microporous membrane is used as a suction filtration membrane, and the modified solution is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled membrane, and vacuum drying is performed at 40-60° C. for 20 h;

[0071] Step 3: Electrochemical phase transition of the membrane modification layer

[0072] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, using metallic lithium as the electrode, and an electrolyte prepared by dissolving 0.5M LiTFSI in DOL / DME (volume ratio 1:1) as the working electrolyte. Three cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally obtain a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation.

[0073] Example 6

[0074] Step 1: Preparation of modified precursor sol

[0075] First, cobalt acetate tetrahydrate, potassium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 1:0.4:85, and reacted at 47° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:110.

[0076] Step 2: Self-assembly modification of the diaphragm

[0077] The modified precursor sol prepared in step 1 was mixed evenly with anhydrous ethanol at a volume ratio of 0.8:1 to obtain a modified solution, and a commercial Celgard-2301 microporous membrane was used as a suction filtration membrane, and the modified solution was used as a filtrate, and vacuum-filtered to obtain a self-assembled membrane, and vacuum-dried at 40-60° C. for 17 h;

[0078] Step 3: Electrochemical phase transition of the membrane modification layer

[0079] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, using metallic lithium as an electrode and an electrolyte prepared by dissolving 1M LiClO4 in EC / DEC / PC (volume ratio 1:1) as a working electrolyte. Two cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V and a scan rate of 1.5mV / s to phase transform the self-assembled membrane, and finally a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation is obtained.

[0080] Example 7

[0081] Step 1: Preparation of modified precursor sol

[0082] First, ferrous acetate tetrahydrate, potassium acetate and anhydrous ethanol are mixed and dissolved in a mass ratio of 0.9:0.4:80, and reacted at 52° C. under normal pressure. After the reaction is complete, the reaction solution is filtered, dried, and crushed to obtain a solid powder. Finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonic treatment is performed until the solid powder is completely dissolved to obtain a modified precursor sol. The mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:100.

[0083] Step 2: Self-assembly modification of the diaphragm

[0084] The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol in a volume ratio of 1:1 to obtain a modified solution, and a commercial Celgard-2400 microporous membrane is used as a suction filtration membrane, and the modified solution is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled membrane, and vacuum drying is performed at 40-60° C. for 20 h;

[0085] Step 3: Electrochemical phase transition of the membrane modification layer

[0086] The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, metallic lithium is used as the electrode, and an electrolyte prepared by dissolving 1M LiTFSI in DOL / DME (volume ratio 1:1) is used as the working electrolyte. Two cycles of lithium insertion reaction are performed at a voltage of 3.0V to -0.2V, with a scan rate of 0.5mV / s, to phase transform the self-assembled membrane, and finally a self-assembled modified polyolefin membrane capable of inhibiting dendrite formation is obtained.

[0087] Example 8

[0088] The battery performance test was carried out on the self-assembled modified polyolefin separators prepared in Examples 1 to 7:

[0089] Button cells were assembled in an argon-filled glove box in the order of lithium sheet, self-assembled modified polyolefin separator (Ф16-14 mm), 60 μL commercial lithium-sulfur electrolyte (1 M LiTFSI dissolved in DOL / DME (volume ratio 1:1), with 1 wt% lithium nitrate added), and lithium sheet (Ф14-12 mm) to test the electrochemical performance.

[0090] The cycle performance test was carried out using a NEWARE system (CT-4008T, Shenzhen NEWARE Electronics Co., Ltd.). The current density was 0.25 mA / cm 2 , capacity is 0.5 mAh / cm 2 Advanced activation for 3 cycles. Tested using 1mA / cm 2 The current density of the cycle test is carried out, and the test results corresponding to Example 1 are as follows Figure 4 As shown. Figure 4 It can be seen that in the electrochemical test, the Li||Li battery equipped with the self-assembled separator of the present invention has excellent performance such as smaller polarization and longer cycle time.

[0091] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the embodiments. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A method for preparing a self-assembled modified polyolefin membrane, characterized in that: The following steps are involved: Step 1: Preparation of modified precursor sol Firstly, a transition metal acetate hydrate and an alkali metal acetate are dissolved in anhydrous ethanol and mixed evenly to obtain a reaction mixture; then the reaction mixture is reacted at 40-80° C. under normal pressure, filtered after the reaction is complete, dried, and crushed to obtain a solid powder; finally, the solid powder is dissolved in deionized water from which oxygen has been removed, and ultrasonication is performed until the solid powder is completely dissolved to obtain a modified precursor sol; In the reaction mixture, the concentration of transition metal ions is 10-40 mmol / L, and the concentration of acetate is 2-2.4 times the concentration of transition metal ions; Step 2: Self-assembly modification of the diaphragm The modified precursor sol prepared in step 1 is mixed evenly with anhydrous ethanol to obtain a modified liquid, a polyolefin microporous filter membrane is used as a suction filtration membrane, and the modified liquid is used as a filtrate, and vacuum filtration is performed to obtain a self-assembled diaphragm, and vacuum drying is performed at 40 to 60° C.; Step 3: Electrochemical phase transition of the membrane modification layer The dried self-assembled membrane prepared in step 2 is placed in a lithium-lithium symmetric battery, and 2 to 5 cycles of lithium insertion reaction are performed at a scan rate of 0.5 to 3 mV / s and a voltage range of 3.0 V to -0.2 V to obtain a self-assembled modified polyolefin membrane; In the lithium-lithium symmetrical battery, the lithium salt concentration of the electrolyte is controlled to be 0.5-1.5 mol / L.

2. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 1, the transition metal acetate hydrate includes one or more of cobalt acetate tetrahydrate, nickel acetate tetrahydrate, and ferrous acetate tetrahydrate.

3. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 1, the alkali metal acetate includes one or more of potassium acetate, sodium acetate, and lithium acetate.

4. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 1, the mass ratio of the solid powder to the deionized water from which oxygen has been removed is 1:80 to 1:

130.

5. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 2, the volume ratio of the modified precursor sol to anhydrous ethanol is 1:0.6 to 1:1.

5.

6. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 2, the polyolefin microporous filter membrane includes one or more of a polyethylene membrane, a polypropylene membrane, a mixed polyolefin membrane, a cellulose membrane, a polyethersulfone membrane, and a polytetrafluoroethylene membrane; And / or, the pore size of the polyolefin microporous filter membrane is 10 to 80 nm.

7. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step 2, vacuum drying is performed at 40-60° C. for 12-24 hours.

8. The method for preparing the self-assembled modified polyolefin membrane according to claim 1, characterized in that: In step three, in the electrolyte of the Li-Li symmetric battery, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl imide), and lithium trifluoromethanesulfonate; the solvent includes one or more of dimethyl carbonate, ethylene carbonate, propylene carbonate, 1,4-dioxolane, diethyl carbonate, dimethyl ether, ethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether. 9 . The self-assembled modified polyolefin membrane prepared according to the method for preparing the self-assembled modified polyolefin membrane according to any one of claims 1 to 8 .

10. Use of the self-assembled modified polyolefin separator according to claim 9 in metal lithium batteries.

Citation Information

Patent Citations

  • Battery diaphragm, preparation method thereof and secondary battery

    CN116093540A

  • Modified diaphragm for lithium metal battery and preparation method of modified diaphragm

    CN117638406A

  • Composite diaphragm for lithium-sulfur battery, preparation method of composite diaphragm and lithium-sulfur battery

    CN117673655A

  • Electrodes for lithium batteries

    US20040191633A1